Politik Representasi Identitas Perempuan dalam Media: Wacana Kritis Pemberitaan KDRT di suara.com - Makiyah, 'Ulya Nurul; Hayya, Luma’ul ‘Adilah; Qisthina, Dwi Sufa Nada (Academic Journal of Da'wa and Communication, 2024)
Domestic violence (DV) is a complex problem with significant implications for the lives of women and children. Women's identities are often portrayed negatively and stereotypically as housewives, caregivers, weak, helpless, and submissive. Men's views tend to see women as sexual objects, sex symbols, objects that reinforce patriarchal patterns, and vulnerable to harassment and violence. This study aims to uncover the politics of women's representation in reporting domestic violence on suara.com. The politics of representation in this context refers to the way the media presents and constructs narratives about violence against women. The focus of this study is to understand how the media depicts cases of domestic violence, especially in the context of women's representation. The research method used is qualitative research with Sara Mills' critical discourse approach. Data were obtained through reading, understanding, recording, and identification using this approach. The results of the analysis show that the media still often depict women in a stereotypical framework that shows them as weak, causing problems, and emotional, for the benefit of the media company itself.